Protective Capacity of Statins during Pneumonia Is Dependent on Etiological Agent and Obesity - Karlsson, Erik A.; Schultz-Cherry, Stacey; Rosch, Jason W. (Frontiers in Cellular and Infection Microbiology, 2018)
Acute respiratory infections are a leading cause of death worldwide. Clinical data is conflicted regarding whether statins improve outcomes for pneumonia. Potential confounding factors including specific etiology of pneumonia as well as obesity could potentially mask protective benefit. Obesity is a risk factor for high cholesterol, the main target for statin therapy. We demonstrate that statin intervention conferred no protective benefit in the context of wild-type mice regardless of infectious agent. Statin intervention conferred either a protective benefit, during influenza infection, or detrimental effect, in the case of pneumococcal infection, in obese animals. These data suggest etiology of pneumonia in the context of obesity could be dramatically altered by the protective effects of statin therapy during bacterial and viral pneumonia.